A fossil Paratrombiinae mite (Actinotrichida: Trombidioidea) from the Rovno amber, Ukraine - Konikiewicz, Marta; Mąkol, Joanna (Zootaxa, 2014)
The first description of a fossil representative of Paratrombiinae from the Rovno amber, Paratrombium rovniense sp. nov., based on an unengorged larva, is provided. The discovery results in a re-definition of the Paratrombiinae and of Paratrombium, which also comprise species with two pectinalae on coxa I.